2018
DOI: 10.1016/j.bbamcr.2018.02.009
|View full text |Cite
|
Sign up to set email alerts
|

γ-Tubulin has a conserved intrinsic property of self-polymerization into double stranded filaments and fibrillar networks

Abstract: γ-Tubulin is essential for microtubule nucleation and also plays less understood roles in nuclear and cell-cycle-related functions. High abundancy of γ-tubulin in acentrosomal Arabidopsis cells facilitated purification and biochemical characterization of large molecular species of γ-tubulin. TEM, fluorescence, and atomic force microscopy of purified high molecular γ-tubulin forms revealed the presence of linear filaments with a double protofilament substructure, filament bundles and aggregates. Filament format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(60 citation statements)
references
References 75 publications
4
56
0
Order By: Relevance
“…We and others have recently reported that γ-tubulin forms a cellular meshwork of γ-strings 57 and γ-tubules 8 . While γ-tubules are polar cytosolic filaments within the γ-string meshwork, γ-strings are detected in both the cytoplasm and the nucleus and are formed of non-polar protein threads that cross the double membrane of the nuclear envelope.…”
Section: Introductionmentioning
confidence: 85%
“…We and others have recently reported that γ-tubulin forms a cellular meshwork of γ-strings 57 and γ-tubules 8 . While γ-tubules are polar cytosolic filaments within the γ-string meshwork, γ-strings are detected in both the cytoplasm and the nucleus and are formed of non-polar protein threads that cross the double membrane of the nuclear envelope.…”
Section: Introductionmentioning
confidence: 85%
“…Part of the cellular pool is folded into γ-tubulin threads called γ-strings by the type II chaperonin CCT. 36 γ-Strings are 4–6 nm in diameter 23 , 28 , 36 , 37 and span from the cytosolic compartment through the nuclear membrane and into the chromatin. A γ-string is very thin and alone can offer little stability.…”
Section: The Cellular Organization Of γ-Tubulinmentioning
confidence: 99%
“…A number of studies in recent years have broadened this view of γ-tubulin [ 9 , 10 , 11 , 14 , 23 , 24 , 25 , 26 , 27 , 28 , 39 , 40 , 41 , 42 , 43 ]. In some cell lines and primary cells, a pool of γ-tubulin in the nuclear compartment [ 27 , 44 , 45 ] has been detected and found to be associated with Rad51, C53, GCP2, GCP3, E2F1, and lamin B1 [ 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Is γ-Tubulin a Sticky Protein Or A Meshwork?mentioning
confidence: 99%
“…An in vivo analysis of zebrafish embryos and in vitro experiments have shown that part of the cellular γ-tubulin pool is folded into γ-strings by the chaperonin CCT [ 39 ]. Experiments on the plant Arabidopsis thaliana have confirmed and further clarified the structure of γ-strings [ 43 ]. γ-Strings are 4 to 6 nm in diameter [ 14 , 28 , 39 , 43 ] and, in animal cells, span from the cytosolic compartment through the membranes and into the chromatin [ 14 , 28 ].…”
Section: Is γ-Tubulin a Sticky Protein Or A Meshwork?mentioning
confidence: 99%